Toward the Sustainable Development of the Fisheries Sector: An Analysis of the Philippine Fisheries Code and the AFMA - Danilo C. Israel; Ruchel Marie Grace Roque (Philippine Institute for Development Studies (PIDS), 1999)
The paper analyzes the Philippine Fisheries Code in relation to the objective of sustainable development in the fisheries sector. The paper finds that some of the provisions in the Code promote sustainable development while a few other provisions are contentuous. It argues that the good provisions be implemented forcefully and immediately by the pertinent offices while the bad provisions be further studied and amended in time, if need be.
Keywords: 330; fisheries sector